2010
DOI: 10.1136/sti.2009.037846
|View full text |Cite
|
Sign up to set email alerts
|

Violence victimisation, sexual risk and sexually transmitted infection symptoms among female sex workers in Thailand

Abstract: Background/objectives Commercial sex work is widely recognized as a primary context for heterosexual transmission of HIV/AIDS in many regions, including Southeast Asia. While violence victimization is considered to compromise women’s ability to protect against HIV and other sexually transmitted infections (STIs), with female sex workers (FSWs) uniquely affected, little research has investigated the role of violence as it relates to sexual risk and STI outcomes among FSWs. The current study sought to compare ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 32 publications
12
111
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14]23,26,46,48,49 Previous studies along Mexico's North Border have contributed to this international consensus by identifying a panoply of associations between criminal justice experiences and behavioral risk factors, including syringe sharing. 29,50,51 We have also observed independent associations between arrest and HIV status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9][10][11][12][13][14]23,26,46,48,49 Previous studies along Mexico's North Border have contributed to this international consensus by identifying a panoply of associations between criminal justice experiences and behavioral risk factors, including syringe sharing. 29,50,51 We have also observed independent associations between arrest and HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Table 1, median age was 33 (interquartile range [IQR], 27-40); 38 % were married and 42 % had children dependents. Most (80 %) engaged in street-based sex work, with a median of 10 h spent on the street daily (IQR, [7][8][9][10][11][12][13][14][15]. Almost half of the respondents (48 %) reported having syringes confiscated in the last 6 months.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Griensven and de Lin van Wijngaarden (2010) all described the syndrome in homosexual and bisexual men and, intravenous drug users, while Harris et al (1983); Padian et al (1991); Cameron et al (1989); Quinn et al (2000) and Decker et al (2010) recognised their mode of transmission through heterosexual activity. Evidences later showed that transmission recipients and haemophiliacs could contract the illness from blood or blood products (CDC, 1982;Peterson, 1992;CDC, 2010) and newborn infants get infected from their mothers' (Ammann et al, 1983;Scarlatti, 1996;Brookmeyer, 1991;Landesman, et al, 1996;Goedert et al, 1989;Mackelprang et al, 2010).…”
mentioning
confidence: 99%